UK Experience of an Alternative ATO Dosing Regimen in APL - Russell, Nigel; Dillon, Richard (Frontiers in Oncology, 2020)
The introduction of all-trans retinoic acid (ATRA), and more recently of arsenic trioxide (ATO) in the treatment of APL, has been instrumental in achieving the high cure rates recently reported. For the majority of patients it is now possible to successfully treat this disease “chemo-free” without the use of cytotoxic chemotherapy as reflected in current clinical guidelines. In the UK our approach for patients with standard risk APL is to treat with ATRA and ATO without the use of cytotoxic chemotherapy. This approach is based on results from two large randomised clinical trials which used different ATO regimens from the GIMEMA APL0406 trial and the attenuated doses used in the UK NCRI AML17 trial. Both trials showed superiority to standard anthracycline-based chemotherapy plus ATRA. In the UK, the National Institute for Clinical Excellence approved both regimens for re-imbursement for standard risk APL. We use the AML17 schedule in standard-risk patients upfront and also in patients with relapsed APL previously treated with chemotherapy or in those with molecular persistence. The treatment of high-risk APL remains an area of contention as ATO is not approved for this indication.. These patients have a greater risk of complications during remission induction with ATO including differentiation syndrome. The optimal approach is to incorporate chemotherapy early into the treatment schedule with either Gemtuzumab Ozogamicin (GO) as in the high-risk arm of the NCRI AML17 trial and MD Anderson Cancer Centre studies or Idarubicin as in the Australian APML4 study.